COOPERATIVE LEARNING METHODS NUMBERED HEAD TOGETHER MODEL TO INCREASE LEARNING ACHIEVEMENT "PPKn" IN HIGH SCHOOL STUDENTS - Mohamad Toha (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
Teaching and learning activities should take into account the characteristics and potential of students. Students can teach each other with other students. A teaching system that provides opportunities for students to collaborate with peers in structured tasks is an important thing to do. Currently, there are still many students who still have difficulty in learning to acquire knowledge. The objectives of this study are (a) to determine the effect of cooperative learning with the Numbered Head Together model on learning outcomes for Civics, (b) to find out how high the level of mastery of Civics subject matter is with the implementation of the Numbered Head Together model of cooperative learning. This research uses two rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection and revision. The targets of this study were students of class XI IPA 1 SMA Negeri 2 Banjar for the 2019/2020 academic year. The data obtained were in the form of post-test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning achievement has increased from cycle I to cycle II, namely, cycle I (80.00%), cycle II (94.29%). The conclusion of this study is that cooperative learning methods can have a positive effect on achievement and learning motivation of XI IPA 1 students and this learning model can be used as an alternative to Pancasila and Citizenship Education learning.